Sex differences between APPswePS1dE9 mice in A-beta accumulation and pancreatic islet function during the development of Alzheimer's disease. (August 2016) - Li, Xin; Feng, Ying; Wu, Wei; Zhao, Jia; Fu, Chunmei; Li, Yang; Ding, Yangnan; Wu, Binghuo; Gong, Yanju; Yang, Guizhi; Zhou, Xue
The pathogenesis of Alzheimer's disease (AD), a type of neurodegenerative disease characterized by learning and memory impairment, is often associated with pathological features, such as amyloid-beta (Aβ) accumulation and insulin resistance. The transgenic mouse, APPswePS1dE9 (APP/PS1), is one of the most commonly used animal models in pathogenesis studies of AD. The purpose of this study is to investigate the sex differences between APP/PS1 mice in the pathogenesis of AD. The impairment of glucose and insulin tolerance was found to develop earlier in male APP/PS1 mice than in females. Plasma insulin levels were significantly decreased in male APP/PS1 mice, while total cholesterol levels in male APP/PS1 mice were higher than those in females. Triglyceride levels in male mice in both the wild-type (WT) and APP/PS1 groups were higher than in their female littermates. Soluble and insoluble Aβ levels in female APP/PS1 mouse brains were higher than those in males. And the learning and memorizing abilities of female APP/PS1 mice were poorer than those of males. Our results concluded that there were sex differences in Aβ formation, pancreatic islet function and insulin sensitivity between male and female APP/PS1 mice during the pathogenesis of AD.